Jamming layered membrane gripper mechanism for grasping differently shaped-objects without excessive pushing force for search and rescue missions. (3rd June 2018) - Fujita, Masahiro; Tadakuma, Kenjiro; Komatsu, Hirone; Takane, Eri; Nomura, Akito; Ichimura, Tomoya; Konyo, Masashi; Tadokoro, Satoshi
ABSTRACT: A gripper comprising a jamming membrane was developed with the capability of grasping collapsible, soft, and fragile objects without applying heavy pressure. In disaster sites, it is necessary for robots to grab various types of objects, such as fragile objects. Deformable grippers that contain bags filled with powder cannot handle collapsible or soft objects without excessive pressure. Changing powder density relatively by changing inner volume is one approach to overcome this problem. By expanding the concept and simplifying the variable inner volume of the gripping mechanism, we developed a jamming membrane comprising the following three layers: outer layer and inner layer made of rubber and a powder layer in between the outer and inner rubber layer. This jamming membrane allows collapsible, soft, or fragile objects to be held securely without applying too much pressure. We designed and developed a prototype of the jamming membrane gripper. Our experiments confirmed the validity of the proposed jamming membrane mechanism. GRAPHICAL ABSTRACT: